Experimental sleep disruption and reward learning: moderating role of positive affect responses. Issue 5 (31st March 2019) - Finan, Patrick H; Whitton, Alexis E; Letzen, Janelle E; Remeniuk, Bethany; Robinson, Mercedes L; Irwin, Michael R; Pizzagalli, Diego A; Smith, Michael T
Abstract: Study Objectives: Sleep disturbances increase vulnerability for depression, but the mechanisms underlying this relationship are not well known. We investigated the effects of experimental sleep disruption on response bias (RB), a measure of reward learning previously linked to depression, and the moderating role of positive affect responses. Methods: Participants ( N = 42) were healthy adults enrolled in a within-subject crossover sleep disruption experiment that incorporated one night of uninterrupted sleep (US) and one night of forced awakenings (FA) in random order. On the day following each experimental sleep night, participants completed a probabilistic reward task to assess RB, and the Positive and Negative Affect Schedule-X. Participants were subgrouped according to positive affect responses: Preserved Positive Affect (i.e. positive affect scores maintained or increased; n = 15) or Reduced Positive Affect (i.e. positive affect scores decreased; n = 27) following FA. Results: Contrary to our hypotheses, across participants, RB did not significantly differ between the US and FA sleep conditions ( p = .67). However, the effect of sleep condition on RB was moderated by positive affect response ( p = .01); those with preserved positive affect showed heightened RB following FA, whereas those with reduced positive affect showed diminished RB following FA. Changes in negative affect between US and FA did not moderate RB. Conclusion: The inability to preserve positive affect through periods of sleep disruption may be a marker of diminished reward learning capability. Understanding how sleep disruption impacts positive affect responses and reward learning identifies a pathway by which sleep disturbances may confer risk for depression.